2023
DOI: 10.1101/2023.08.14.553290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From paralogy to hybridization: Investigating causes of underlying phylogenomic discordance using the complex genusPackera(Senecioneae; Asteraceae)

Abstract: Premise of the study: Underlying discordance in phylogenomic studies is becoming more common, and the answer is not as simple as adding more data. Biological processes such as polyploidy, hybridization, and incomplete lineage sorting are main contributors to these issues and must be considered when generating phylogenies. Otherwise, interpretations of evolutionary relationships could be misleading. Methods: To obtain a better understanding of potential gene flow and its effect on phylogenetic trees, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Similar conclusions have been found in other groups (e.g., Sessa et al, 2012 ; Vargas et al, 2017 ; Morales‐Briones et al, 2018 ). Interestingly, a recent study in Packera showed that low support or discordant clades may be the result of ancient reticulation events in Packera 's history (Moore‐Pollard and Mandel, 2023b ), ultimately influencing the relationships and support within the species trees. We hypothesize that using Comp‐ParaLoss‐1272 will not only directly reduce issues associated with polyploidy, but also reduce issues from hybridization even if not addressed directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions have been found in other groups (e.g., Sessa et al, 2012 ; Vargas et al, 2017 ; Morales‐Briones et al, 2018 ). Interestingly, a recent study in Packera showed that low support or discordant clades may be the result of ancient reticulation events in Packera 's history (Moore‐Pollard and Mandel, 2023b ), ultimately influencing the relationships and support within the species trees. We hypothesize that using Comp‐ParaLoss‐1272 will not only directly reduce issues associated with polyploidy, but also reduce issues from hybridization even if not addressed directly.…”
Section: Discussionmentioning
confidence: 99%
“…While removing paralogs from a data set may alleviate issues associated with ortholog determination in phylogenomic studies, it is important to note that paralogs are still reflective of the true evolutionary history of genes within some groups, including Packera . For example, hybridization and polyploidy are common in Packera , with around 40% of all Packera members exhibiting polyploidy (Trock, 1999 ; Moore‐Pollard and Mandel, 2023a , 2023b ), and thus paralogs are expected in the data set as it reflects the true evolutionary history of the group. Therefore, removing paralogs can remove full gene histories, impacting the ability to accurately model processes like reticulation and polyploidy.…”
Section: Discussionmentioning
confidence: 99%